Mycoplasma hominis. A cause of neonatal meningitis. Issue 3 (March 1979) - Gewitz, M; Dinwiddie, R; Rees, L; Volikas, O; Yuille, T; O'Connell, B; Marshall, W C
Abstract : Two cases of Mycoplasma hominis meningitis in the newborn are described. These infants demonstrate the need to consider M. hominis as a cause of neonatal meningitis, especially if the Gram stain is negative, conventional cultures yield no growth, and there is a history of maternal infection. CSF cultures on appropriate medium can quickly confirm the diagnosis.